RESPONSES TOWARD INDUCTIVE AND DEDUCTIVE METHOD IN TEACHING WRITING - Dedi Turmudi (Premise: Journal of English Education and Applied Linguistics, 2012)
This study discusses the effects of inductive and deductive approaches in teaching writing to students' understanding and learning achievements at the 2011 Academic Year Muhammaadiyah University of Metro. This approach is like the teacher centered learning model, a student-centered learning model (Students Centered Approach). To illustrate the effects of this approach, researchers conducted research with the Lesson Study approach in which the inductive and deductive approaches were applied sequentially and separately. There are 44 UM Metro semester III students who are taken as the research subjects. They experienced the teaching and learning process in two cycles: the first cycle with an inductive approach and the second cycle with a deductive approach. The purpose of this research is to describe and explore how deep the effects of the inductive and deductive approaches are. The results showed that the deductive approach proved to be more effective and had a positive effect on the comprehension of students' understanding in the writing subject 2 with a ratio of 23.8% positive for the inductive approach and 58.2% positive for the deductive approach. It implies that the deductive approach mainly occupy the mindset of the Indonesian EFL students.